2007
DOI: 10.1039/b610375h
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of the blue-light sensing protein YtvA reveals a competitive interface for LOV—LOV dimerization and interdomain interactions

Abstract: The Bacillus subtilis protein YtvA is related to plant phototropins in that it senses UVA-blue-light by means of the flavin binding LOV domain, linked to a nucleotide-binding STAS domain. The structural basis for interdomain interactions and functional regulation are not known. Here we report the conformational analysis of three YtvA constructs, by means of size exclusion chromatography, circular dichroism (CD) and molecular docking simulations. The isolated YtvA-LOV domain (YLOV, aa 25-126) has a strong tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
104
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(112 citation statements)
references
References 72 publications
7
104
1
Order By: Relevance
“…This might happen because the distances between the lysines decrease in the photoexcited state so that the crosslinking reaction is more probable (see figure in the graphical abstract). Such a photoinduced increase of the LOV-LOV interaction might be important for signal transduction if, as suggested, [30] the autophosphorylation of phot is in fact a mutual cross-phosphorylation of a pair of phot proteins.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This might happen because the distances between the lysines decrease in the photoexcited state so that the crosslinking reaction is more probable (see figure in the graphical abstract). Such a photoinduced increase of the LOV-LOV interaction might be important for signal transduction if, as suggested, [30] the autophosphorylation of phot is in fact a mutual cross-phosphorylation of a pair of phot proteins.…”
Section: Discussionmentioning
confidence: 91%
“…[23] The tendency of LOV domains to form dimers has been noticed previously. [25][26][27][28][29][30] Salomon et al showed by using size-exclusion chromatography that phot1-LOV1 dimerizes, but LOV2 stays monomeric. [25] In this work the authors suggested that LOV1 is responsible for phot dimerization, which would provide a possible functional role for the tandem organization of LOV domains in phot proteins.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the crystal structure of YtvA-LOV, the linker instead protrudes outside of the LOV core, and the ␤-scaffold is engaged in the tight LOV-LOV dimer (20). In full-length YtvA, the ␤-scaffold is involved in intraprotein/interdomain interactions, and there is no light-induced unfolding of the linker, whose exact orientation remains to be determined (21).…”
Section: Aureo: Not Just Another Leucine Zippermentioning
confidence: 99%